Mockingbird songs my friendship with Harper Lee - Flynt, Wayne 1940-; Lee, Harper 1926-2016 (HarperCollins Publishers, 2017)
"A memoir of Wayne Flynt's friendship with Harper Lee, centered on a collection of letters between Harper Lee, her sisters, ... Wayne Flynt, and his wife"...